What Paul really said about women : an apostle's liberating views on equality in marriage, leadership, and love : with study questions - Bristow, John Temple ([San Francisco] : HarperSanFrancisco, 1991)
Reassesses the message of Paul's epistles, arguing that his philosophies were more egalitarian than is commonly thought.
Reprint. Originally published: San Francisco : Harper & Row, 1988.
Includes bibliographical references (pages 120-126) and indexes.
Keywords: Paul, -- the Apostle, Saint; Women -- Biblical teaching; Bible. -- Criticism, interpretation, etc